Survey of coagulation factor concentrates tender and procurement procedures in 38 European Countries. (20th May 2015) - O'Mahony, B.; Noone, D.; Prihodova, L.
<x xml:space="preserve">Abstract</x> Introduction Procurement of coagulation factor concentrates (CFCs) for the treatment of haemophilia is a vital process that determines the quantity and quality of factor replacement therapy. Aim The aim of this study was to examine the different tender and procurement systems used in Europe for the procurement of CFCs and the outcomes produced by the various systems. Methods The survey questionnaire consisted of 30 items and explored various aspects of the procurement process including the prices of CFCs. In 2014, the survey was sent out by the European Haemophilia Consortium (EHC) to 45 national haemophilia patient organizations affiliated to the EHC in all European countries as well as to a designated clinician familiar with the procurement process. Results The survey was completed by 38 European countries. Nineteen countries use a tender process, 17 an alternative procurement process and 2 use a combination of methods. A wide variety of agencies and individuals are involved in the process. Factors associated with optimum outcome and lower prices include a tender process with a specific legal framework and a tender board including haemophilia clinicians and patient organization representatives. Safety was reported as the most important selection criterion but given the safety profile of almost all currently licensed products, price was the main criterion used in many countries. Conclusion The involvement of both clinicians and patient organizations greatly improves the outcome of a tender or procurement process, as does the presence of a legal framework that governs the process.